2020
DOI: 10.1177/1539449220961077
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of Turkish Myasthenia Gravis-Activities of Daily Living Scale

Abstract: Linguistic, reliable, and valid secondary efficacy measures are important in clinical settings and studies. The aim of the study is to report test–retest reliability and construct validity of Turkish version of Myasthenia Gravis-Activities of Daily Living Scale (MG-ADL-T) in Myasthenia Gravis (MG) patients. Fifty-two ocular and generalized individuals with MG, applying to rehabilitation center, were included in the study. MG-ADL-T, MG quality-of-life questionnaire (MG-QoL), MG composite (MGC), quantitative MG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 33 publications
(49 reference statements)
2
5
0
Order By: Relevance
“…18 The internal consistency of the Italian, Arabic, and Turkish versions of MG-ADL was different. 15 , 16 , 19 The internal consistency of the Turkish version of MG-ADL was obtained 0.67, similar to the Mohd Thabit et al study.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…18 The internal consistency of the Italian, Arabic, and Turkish versions of MG-ADL was different. 15 , 16 , 19 The internal consistency of the Turkish version of MG-ADL was obtained 0.67, similar to the Mohd Thabit et al study.…”
Section: Discussionsupporting
confidence: 85%
“…Several studies have demonstrated excellent test-retest reliability in the different languages. 15 - 17 , 19 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MG-QOL15 is a speci c assessment scale of the quality-of-life speci c assessment scale for myasthenia gravis which is most widely used, cross-culturally validated [11][12][13][14][15], and encompasses the physical, psychological, and social dimensions of quality-of-life assessment. MG-ADL is used as an extension of the quantitative MG scoring system (QMG) (a standardized scale for the objective measurement of muscle strength and endurance in MG-involved muscle groups) to assess the current severity of the disease in patients with myasthenia gravis.…”
Section: Discussionmentioning
confidence: 99%
“…The MG-ADL is responsive to clinical improvement, and it can be also used to assess the progression of the disease and to determine the effectiveness of the treatment (6-8). This scale has been translated into other languages, and those versions have been validated (9)(10)(11)(12). Due to the fact that there is no MG-specific assessment tool for the severity of symptoms and their effect on daily activities in the Latvian language, our aim was to translate and adapt the MG-ADL to Latvian and to evaluate the Latvian version (MG-ADL-L) in terms of construct validity and reliability.…”
Section: Introductionmentioning
confidence: 99%